THE CONCEPTS AND METHODS OF DZAWIL ARHAM HERITAGE CALCULATION: Analysis and Practice: Analysis and Practice - Ritonga, Raja (Nurani, 2021)
Dzawilarham is seen as a marginalized heir group. The position of the inheritance rights is a struggle between the pro and the contra among the ulama. The distribution of inheritance to the dzawilarham group by agreeing their inheritance rights opens the door of a goodness. Hifzu an-nasl (guarding descent) is one of the maqashid of Islamic law. The existence of dzawilarham as a family, relative or descendant deserves to be protected and embraced. This research is to describe the position of dzawilarham and to explain the concepts and practical methods in counting the parts of dzawilarham in Islamic inheritance. This research method uses literature study, namely conducting research on a number of references that are relevant to the discussion. The data were described and analyzed in a qualitative form. The result explain that the dzawilarham kinship pathway is bilateral, through the male route and the female route. The inheritance of dzawilarham is agreed by the majority of friends and ulamamazhab. The concept and determination of the inheritance of dzawilarham has three characteristics, mazhabahlu at-tanzil, mazhabahlu al-qorobah and mazhabahluar-rahmi. At the completion of the count of inheritance, the ahluar-rahmimazhab equalizes all the positions and the portion of the heirs. Meanwhile, the ahlu at-tanzilmazhab provides the portion of the dzawilarham according to the part of origin. While the ahlu al-qorobahmazhab completes the count of dzawilarham with the concept of inheritance of ashobah, close relatives block those who are far away. Keywords: ahlu al-qorobah, ahlu at-tanzil, ahluar-rahmi, dzawilarham, heirs